2016
DOI: 10.17265/1539-8072/2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Is Recast the Most Effective Type of Corrective Feedback?—Under Cognitive and Sociolinguistic Approach

Abstract: Currently, there are a variety of researches on corrective feedback, especially on recasts. Most of researches are experiment-based and depend on the certain context. This paper addresses the question of "Is recast the most effective form of corrective feedback?" by two of Second Language Acquisition (SLA) approaches: cognitive approach and sociolinguistic approach. Empirical research will be used as complement. Theoretically speaking, SLA hypotheses in cognitive approach exist disagreements. Interaction hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Furthermore, if teachers only recast a single pronunciation, it will not give students an idea to use that word based on the context. Teachers need to adopt more various modeling that can accommodate some social factors e.g., teaching methods, classroom dynamics, individual anxiety level, and preference among the students which influence learning (Bing-Jie, 2016). Different modeling such as open-ended questions, re-voicing, reasoning, etc.…”
Section: Corrective Feedback In Applied English Classmentioning
confidence: 99%
“…Furthermore, if teachers only recast a single pronunciation, it will not give students an idea to use that word based on the context. Teachers need to adopt more various modeling that can accommodate some social factors e.g., teaching methods, classroom dynamics, individual anxiety level, and preference among the students which influence learning (Bing-Jie, 2016). Different modeling such as open-ended questions, re-voicing, reasoning, etc.…”
Section: Corrective Feedback In Applied English Classmentioning
confidence: 99%
“…Rassaei (2015) found that for high-anxiety learners, recasts corrective feedback gives more significant benefit rather than metalinguistic corrective feedback. Recasts is defined as reformulates all part of the incorrect word or phrase, to show the correct form without explicitly identifying error (Lee in Bing-Jie, 2016). In learning language elements, recasts can be used as one of the strategies to treat high-anxiety learners.…”
Section: Pupil: International Journal Of Teaching Education and Learning Issn 2457-0648mentioning
confidence: 99%
“…Educators and students felt that technology were useful in delivering feedback. Even, video feedback is better than written feedback in speaking (Bing-Jie, 2016;Tseng & Yeh, 2019;Vries, Cucchiarini, Strik, Hout, 2019). In 2020, Chekol (2020) examined the effect of peer feedback on speaking and their perceptions.…”
Section: Introductionmentioning
confidence: 99%